Neuropharmacological efficacy of metformin for stroke in rodents: A meta-analysis of preclinical trials - Fu, Wenqiao; Tang, Yin; Che, Xudong; Tan, Jiahe; Ma, Yinrui; He, Zhaohui (Frontiers in Pharmacology, 2022)
Background: Stroke, including ischemic stroke, intracerebral hemorrhage (ICH) and subarachnoid hemorrhagic (SAH), remains leading causes of mortality globally. Patients with different stroke subtypes reported similar detrimental effects in multiple fields of health. Previous researches had shown that metformin has a neuroprotective role in experimental stroke animal models. But a preclinical study for quantitative analysis of metformin on treating Stroke is still lacking. Therefore, we performed a meta-analysis to evaluate the efficacy of metformin in improving prognosis of stroke rodents. Methods: We retrieved relevant preclinical trials from PubMed, EMBASE and Web of Science. Metformin compared with vehicle using the standardized mean difference (SMD) and corresponding confidence interval (CI), were assessed by neurological score (NS), brain water content (BWC), infarct size, rotarod test, TUNEL, neuron quantity, microglia quantity and p-AMPK levels. Quality was assessed adopting SYRCLE’s risk of bias tool. Results: Totally, 15 articles published from 2010 through 2022 were included in our meta-analysis. We demonstrated the metformin group has statistically significant differences compared to the control group in NS (SMD −1.45; 95% CI −2.32, −0.58; p =0.001), BWC (SMD −3.22; 95% CI −4.69, −1.76; P < 0.0001), infarct size (SMD −2.90; 95% CI −3.95, −1.85; P < 0.00001), rotarod test (SMD 2.55; 95% CI 1.87, 3.23; P < 0.00001), TUNEL (SMD -3.63; 95% CI -5.77, -1.48; P =0.0009), neuron quantity (SMD 3.42; 95% CI 2.51, 4.34; P < 0.00001), microglia quantity (SMD -3.06; 95% CI -4.69, -1.44; P =0.0002) and p-AMPK levels (SMD 2.92; 95% CI 2.02, 3.82; P < 0.00001). Further, sensitivity analysis and stratified analysis were conducted for heterogeneous outcome indicators. Conclusions: Overall, metformin treatment dramatically improves severe outcomes of stroke. Despite animal studies contain limitations, our systematic review may provide a vital reference for future high-quality preclinical trials and clinical use.